1995
DOI: 10.1016/0039-6028(95)00378-9
|View full text |Cite
|
Sign up to set email alerts
|

Oxide-thickness dependence of second harmonic generation from thick thermal oxides on Si(111)

Abstract: W e show here that the oxide-thickness dependence o f the s-poîarized SHG from S i ( l l l ) covered with a thick thermal oxide is completely described by multiple reflections in the oxide film. For the p-polarized response, a strong enhancement with thickness is observed, which cannot be explained in this way. These measurements show that one should be cautious in analyzing the SHG from a buried interface, and carefully take into account the linear optics involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1996
1996
2004
2004

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 17 publications
(17 reference statements)
0
9
0
Order By: Relevance
“…For a given temperature the etch speed was constant, i.e. no speed changes were found in etching different oxide thicknesses [10,11]. This allows to obtain the oxide thickness from the etching times.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…For a given temperature the etch speed was constant, i.e. no speed changes were found in etching different oxide thicknesses [10,11]. This allows to obtain the oxide thickness from the etching times.…”
Section: Methodsmentioning
confidence: 99%
“…SHG has recently been used to study a number of properties of the S i-S i0 2 interface, including steps and kinks [4,5], strain [6,7], preparation and roughness [8] and electric fields [9]. Recently we have shown that the strong thickness dependence of the s-polarized SHG from thick ther mal oxides on S i( l ll ) is completely explained by linear optics, due to multiple reflections in the oxide layer [10,11], The model combined the calculation of the Fresnel coefficients for the three-layer system (air-oxide-silicon) [12], with the well-know phe nomenological model for SHG [13][14][15][16]. It was also shown that the amplitude of the SHG signal from thin (~ 2 nm) oxides depends on the thermal history of the oxide [10].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…where the integration is taken over The SHG from S i-S i0 2 interfaces depends on the silicon ox ide thickness due to multiple reflections in the S i0 2 layer [11,12]. The S i0 2 layer also affects the electric field inside the Si through the voltage drop across the oxide and because of the presence o f charge located at the buried S i-S i0 2 interface a n d /o r trapped in the S i 0 2 layer.…”
Section: Theorymentioning
confidence: 99%